The BH3 Mimetic Obatoclax Accumulates in Lysosomes and Causes Their Alkalinization. - Vasileios A Stamelos (PLoS ONE, 2016)
Obatoclax belongs to a class of compounds known as BH3 mimetics which function as antagonists of Bcl-2 family apoptosis regulators. It has undergone extensive preclinical and clinical evaluation as a cancer therapeutic. Despite this, it is clear that obatoclax has additional pharmacological effects that contribute to its cytotoxic activity. It has been claimed that obatoclax, either alone or in combination with other molecularly targeted therapeutics, induces an autophagic form of cell death. In addition, obatoclax has been shown to inhibit lysosomal function, but the mechanism of this has not been elucidated. We have evaluated the mechanism of action of obatoclax in eight ovarian cancer cell lines. Consistent with its function as a BH3 mimetic, obatoclax induced apoptosis in three cell lines. However, in the remaining cell lines another form of cell death was evident because caspase activation and PARP cleavage were not observed. Obatoclax also failed to show synergy with carboplatin and paclitaxel, chemotherapeutic agents which we have previously shown to be synergistic with authentic Bcl-2 family antagonists. Obatoclax induced a profound accumulation of LC-3 but knockdown of Atg-5 or beclin had only minor effects on the activity of obatoclax in cell growth assays suggesting that the inhibition of lysosomal function rather than stimulation of autophagy may play a more prominent role in these cells. To evaluate how obatoclax inhibits lysosomal function, confocal microscopy studies were conducted which demonstrated that obatoclax, which contains two basic pyrrole groups, accumulates in lysosomes. Studies using pH sensitive dyes demonstrated that obatoclax induced lysosomal alkalinization. Furthermore, obatoclax was synergistic in cell growth/survival assays with bafilomycin and chloroquine, two other drugs which cause lysosomal alkalinization. These studies explain, for the first time, how obatoclax inhibits lysosomal function and suggest that lysosomal alkalinization contributes to the cytotoxic activity of obatoclax.